Translation Process in Rendering Source Language Spoken Words or Phrases to Target Language Items: Semantic or Communicative Approach - Eskandari, Ali; Panahbar, Ehsan (Richtmann Publishing, 2012)
This paper discusses the translation of spoken words and phrases from English to Persian. Verbal communication isone of the aspects of culture, translation of which really matters in intercultural studies. So, in order to evaluate the efficacy ofthis transfer from source language to target language, we take Newmark’s communicative and semantic approach. To conductthis research, 10 MA students of translation studies are picked and asked to translate 25 sentences each of which containsspoken words or phrases. Based on Newmark, sentences should be rendered into target language communicatively andparticipants rendered only 31% of the items communicatively.